Tinjauan Organ Jantung sebagai Pusat Kehidupan dalam Sistem Kardiovaskular - Feni Atika Tsuroyya; Khotimah Nur Ramadhani; Elsa Oktavia Ramadhani; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
The heart is a vital organ that plays a crucial role in the circulatory system, responsible for pumping oxygen-rich blood and nutrients throughout the body and returning blood containing carbon dioxide to the lungs. Anatomically, the heart consists of four chambers. The coronary vascular system supplies oxygen and nutrients to the heart muscles. The physiology of the heart involves the cycle of heart muscle contraction (systole) and relaxation (diastole), heart rate regulation, and the electrical conduction system that coordinates the heartbeat. Coronary artery disease (CAD) is a disorder of the coronary blood vessels due to atherosclerosis, causing narrowing or blockage of the arteries, hindering blood flow, and leading to ischemia. Prevention of CAD can be done by maintaining a healthy diet, exercising regularly, avoiding smoking, and controlling blood pressure, cholesterol, and blood sugar levels. Understanding the anatomy, physiology, and coronary artery disease is essential for maintaining heart health and preventing cardiovascular disorders.